(untitled) (Texas Journal of Philology, Culture and History, 2026)
This article examines the representation of denotative and connotative meanings in the translation of financial and economic texts. The study focuses on how economic terms, formal expressions, evaluative units, and stylistic devices are rendered in translation with semantic accuracy. Although financial and economic texts primarily aim to convey precise conceptual and logical information, in some cases connotative meaning, including evaluation, expressiveness, pragmatic effect, and authorial attitude, also plays an important role. The article argues that denotative meaning is mainly realized through terminological precision and semantic equivalence, whereas connotative meaning emerges through context, style, discourse environment, and pragmatic function. In addition, the paper illustrates, with examples, such issues as semantic loss, stylistic neutralization, excessive generalization, and weakening of emotionalexpressive coloring in the translation of financial and economic units between English and Uzbek. The study concludes that in the translation of financial and economic texts, not only terminological consistency but also the preservation of the communicative-pragmatic load of the text is an essential condition for translation adequacy.